FACTORS AFFECTING DIVIDEND POLICY WITH BUSINESS RISK AS MODERATION VARIABLES - Hastuti, Rini Tri; Rasyid, Ardhiansyah; Pambudi, Ari (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of liquidity, profitability, growth in assets on dividend policy and also the effect of moderating variables on business risk. The research data is data on manufacturing companies listed on the IDX in the form of financial statements for 2018-2020. The sample was selected using purposive sampling technique and obtained a sample of 38 companies. The research data is panel data which is processed using Eviews 12. The results of this study are profitability has a negative and significant effect on dividend policy. Liquidity and growth in assets have no significant effect on dividend policy. Meanwhile, the moderating variable of business risk can be moderated by weakening the relationship between growth in assets and dividend policy. However, the moderating variable of business risk cannot moderate the relationship between liquidity and profitability to dividend policy.